Manufacturing and structural performance of glass-fiber-reinforced precast-concrete boat ramp planks. (December 2020) - Manalo, A.C.; Alajarmeh, O.; Cooper, D.; Sorbello, C.D.; Weerakoon, S.Z.; Benmokrane, B.
Abstract: Glass-fiber-reinforced-polymer (GFRP) bars are an ideal solution for eliminating the problems of steel corrosion in reinforced-concrete structures exposed to marine environments. The potential long-term benefits of the reduced maintenance costs and increased service life of GFRP-reinforced concrete structures have not been fully realized due to these reinforcing materials being more costly than steel bars. This study aims to demonstrate the cost-effectiveness of GFRP bars as internal reinforcement in precast-concrete boat-ramp planks. This is the first study that provided a comparative evaluation of the manufacturing and structural performance of planks reinforced with GFRP bars or galvanized-steel bars to fully convince engineers and asset owners of the economic benefits of specifying and using GFRP bars in infrastructure projects. The results of the study revealed that the fabrication and installation of the reinforcing mesh constituted the main differences between planks reinforced with GFRP or galvanized steel. Overall, fabricating precast-concrete boat-ramp planks with two layers of GFRP bars required less labor and equipment, and yielded better serviceability and structural performance than the current plank design using galvanized steel. These benefits led to approval and publication of the standard drawings for a new plank design for implementation in boating-infrastructure projects in Australia.